Suture Granuloma Showing False-Positive Findings on FDG-PET - Kohei Takahara; Hiroaki Kakinoki; Saya Ikoma; Kazuma Udo; Shohei Tobu; Yuji Satoh; Yuji Tokuda; Mitsuru Noguchi; Shigehisa Aoki; Jiro Uozumi (Case Reports in Urology)
We report a case of a 33-year-old male with a mixed germ-cell testicular tumor. Postoperative follow-up FDG-PET revealed concentration of FDG in the left inguinal area which is not tumor metastasis or local recurrence but suture reactivity granuloma. In this paper, we reviewed suture granulomas associated with false-positive findings on FDG-PET after surgery. If FDG-PET will be used more frequently in the future, it will be necessary to refrain from using silk thread in order to prevent any unnecessary surgery.